Development of LKPD With A Contextual Approach to Material Opportunities In SMP - Mandasari, Arlina (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2022)
The formulation of the problem from this research is how is the LKPD developed using a contextual approach to opportunity material in junior high school? This study aims to obtain LKPD with a contextual approach to the material opportunities in junior high school. The development of this research uses the Thiargarajan, Semmel and Semmel development model, which is a modified 4-D model. The development process consists of four stages, namely: define, design, develop, and disseminate. However, this research did not reach the disseminate stage due to time constraints. Based on the results of the validator assessment questionnaire for Student Worksheets and lesson plans, the values ??obtained from validators from media experts, material experts and math teachers with an average score of 4.14 and 4.06 with valid criteria